Antithrombotic treatment with direct‐acting oral anticoagulants in patients with splanchnic vein thrombosis and cirrhosis. (19th November 2016) - De Gottardi, Andrea; Trebicka, Jonel; Klinger, Christoph; Plessier, Aurélie; Seijo, Susana; Terziroli, Benedetta; Magenta, Lorenzo; Semela, David; Buscarini, Elisabetta; Langlet, Philippe; Görtzen, Jan; Puente, Angela; et al.
Abstract: Background: Direct‐acting oral anticoagulants (DOACs) are used in patients with splanchnic vein thrombosis (SVT) and cirrhosis, but evidence for safety and efficacy in this setting is limited. Our aim was to identify indications and reasons for starting or switching to DOACs and to report adverse effects, complications and short‐term outcome. Methods: Data collection including demographic information, laboratory values, treatment and complications through the Vascular Liver Disease Interest Group Consortium. Results: Forty‐five centres (90%) of the consortium completed the initial eCRF. We report here a series of 94 patients from 17 centres. Thirty‐six patients (38%) had cirrhosis. Child‐Pugh score was 6 (range 5‐8), and MELD score 10.2 (range 6‐19). Indications for anticoagulation were splanchnic vein thrombosis (75%), deep vein thrombosis (5%), atrial fibrillation (14%) and others (6%). DOACs used were rivaroxaban (83%), dabigatran (11%) and apixaban (6%). Patients were followed up for a median duration of 15 months (cirrhotic) and 26.5 months (non‐cirrhotic). Adverse events occurred in 17% of patients and included one case of recurrent portal vein thrombosis and five cases of bleeding. Treatment with DOACs was stopped in three cases. The major reasons for choosing DOACs were no need for monitoring or inadequacy of INR to guide anticoagulation in cirrhotic patients. Renal and liver function did not change during treatment. Conclusions: A consistent number of patients with SVT and/or cirrhosis are currently treated with DOACs, which seem to be effective and safe. These data provide a basis for performing randomized clinical trials of DOACs vs. low molecular weight heparin or vitamin K antagonists.